1994
DOI: 10.1002/eji.1830241236
|View full text |Cite
|
Sign up to set email alerts
|

On the various manifestations of spontaneous autoimmune diabetes in rodent models

Abstract: Autoimmune (type 1) diabetes mellitus in mouse, rat, and humans shares several features, including T lymphocyte infiltration into pancreatic islets and a dependence on permissive class II major histocompatibility complex (MHC) alleles. We report here on an experimental model involving mice that express influenza hemagglutinin (HA) under the control of the insulin promoter and, at the same time, a transgenic class II MHC-restricted T cell receptor (TcR) specific for an HA peptide. These mice spontaneously devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…To determine whether CD8 ϩ T cells in NOD mice undergo tolerance to a model pancreatic Ag, we produced NOD mice expressing the same InsHA transgene (NOD-InsHA). NOD-InsHA females develop spontaneous diabetes at a similar rate and incidence as normal NOD females (70% incidence by 28 wk of age) (28). Also, the level of HA expression on pancreatic ␤ cells is similar for NODInsHA and BALB-InsHA mice, as measured by flow cytometry using anti-HA Abs (data not shown).…”
Section: Ha-specific Cd8 ϩ T Cells Persist In Nod-inshamentioning
confidence: 70%
“…To determine whether CD8 ϩ T cells in NOD mice undergo tolerance to a model pancreatic Ag, we produced NOD mice expressing the same InsHA transgene (NOD-InsHA). NOD-InsHA females develop spontaneous diabetes at a similar rate and incidence as normal NOD females (70% incidence by 28 wk of age) (28). Also, the level of HA expression on pancreatic ␤ cells is similar for NODInsHA and BALB-InsHA mice, as measured by flow cytometry using anti-HA Abs (data not shown).…”
Section: Ha-specific Cd8 ϩ T Cells Persist In Nod-inshamentioning
confidence: 70%
“…1-3). The disparate effects of epithelial and dendritic cells have been attributed to differences in various cell surface molecules involved in cell-cell interactions, such as LFA-1͞ICAM-1 (23-25), CD28͞B7.1 (26,27), CD40͞gp39 (28,29), Fas͞FasL (30), and CD30͞CD30L (31). Experiments with knockout mice and specific inhibitors have suggested a role for these molecules in thymic selection, but also revealed that they are not always absolutely necessary (23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The TCR-HA Tg Balb/c mice, expressing 14.3d TCR-HA recognizing the immunodominant CD4 T cell epitope of hemagglutinin (HA110-120) of A/PR/8/34 influenza virus in association with I-E d and Ins-HA Tg mice (B10.D2 mice), expressing the HA from the same virus in pancreatic β-cells under the rat insulin promoter were used [3,4]. Since the Ins-HA+/+ Tg mice were homozygous, and the TCR-HA+/-Tg mice were heterozigous, the offsprings were Ins-HA+/-, TCR-HA+/-dTg mice (which developed diabetes) or InsHA+/-, TCR-HA-/-single Tg mice (control group which did not develop diabetes) [5,6].…”
Section: Micementioning
confidence: 99%